Immediate and short-term effects of pile-driving on Hector’s dolphin in Lyttelton Harbour, Aotearoa New Zealand - Deanna M. Clement; Heloise Pavanato; Crystal Lenky; Matthew K. Pine (Frontiers in Marine Science, 2025)
Ports in Aotearoa New Zealand have or are currently undergoing extensive infrastructure developments to accommodate the global trend in larger commercial vessels and cruise ships. With no national standards for underwater noise, Lyttelton Port Company is the first Aotearoa New Zealand port to undertake monitoring to assess pile-driving generated noise effects on local Hector’s dolphins, an endemic and nationally vulnerable species. The immediate and shorter-term responses of this species were monitored with autonomous underwater recorders and assessed to understand how dolphins reacted to pile-driving activities. General and site-specific model results indicated that as sound exposure levels from impact pile-driving increased, declines in dolphin detections varied spatially with immediate declines occurring at sites less than 1km for the source. Declines in detections were still apparent up to 2km, but more evident with greater noise exposure levels and in warmer water conditions. Once piling ceased for a day, Hector’s dolphins moved back into inner harbor waters within hours, and acoustic detections returned to within pre-piling levels gradually over a few days. While there is no evidence that dolphins abandoned the port region over the construction period, our findings established a longer-term decline in dolphin detections coinciding with the 2019 construction period that had not returned to pre-construction levels by May 2020. Despite evidence that mitigation measures were successful at protecting against auditory injury impacts, additional measures are warranted for future port infrastructure developments to avoid short and longer term impacts on Hector’s dolphin use of the harbor and while Aotearoa New Zealand develops or adopts national underwater noise guidelines.

Density and Abundance Estimation of Amazonian River Dolphins: Understanding Population Size Variability - Mariana Paschoalini; Fernando Trujillo; Miriam Marmontel; Federico Mosquera-Guerra; Renan Lopes Paitach; Heloise Pavanato Julião; Gabriel Melo Alves dos Santos; Paul André Van Damme; André Giovanni de Almeida Coelho; Mariana Escobar Wilson White; Alexandre Novaes Zerbini (Journal of Marine Science and Engineering, 2021)
The dolphins Inia geoffrensis—boto and Sotalia fluviatilis—tucuxi are threatened cetaceans inhabiting river ecosystems in South America; population numbers are still lacking for many areas. This paper provides density and abundance estimations of boto and tucuxi in 15 rivers sampled during the past nine years as part of a multinational research alliance. Visual boat-survey data collection protocols and analyses have been developed since 2012 (based on Distance Sampling methods) and recently reviewed (2019) to improve robustness and comparability. Differences across the sampled rivers and the analyzed river basins (Amazon and Orinoco) pointed to a density/population size gradient with lower densities and abundances observed in the Orinoco basin (0.9–1.5 ind./km²), passing through the eastern Amazon basin (2–5 ind./km²), and the largest numbers found at the central Brazilian Amazon (lower Purus River—2012 (14.5 boto/km², N = 7672; 17.1 tucuxi/km², N = 9238)). However, in other parts of the central Amazon, the density of dolphins was smaller than expected for high productive whitewater rivers (1–1.7 ind./km² in the Japurá and Solimões rivers). We attributed these differences to specific features of the basin (e.g., hydro-geomorphology) as well as to the cumulative effects of anthropogenic activities.

Prediction of humpback whale group densities along the Brazilian coast using spatial autoregressive models - Heloise J. Pavanato; Fernando P. Mayer; Leonardo L. Wedekin; Márcia H. Engel; Paul G. Kinas (Marine Mammal Science, 2018)
At the breeding grounds of most baleen whales the patchiness and gaps in spatial distribution results from interactions between behavior patterns and environmental conditions. We evaluated the influence of environmental factors (bathymetry and distance from shore with quadratic terms, and wind speed), effort, and spatial autocorrelation effects to predict humpback whale group density in the Southwest Atlantic Ocean. Count data of groups by grid cells were fitted with conditional autoregressive models (CAR). Bayesian inference was performed via integrated nested Laplace approximation. The best‐fit model contained distance from shore and its quadratic term, bathymetry, and the autoregressive component. Occupancy probability was high for the Abrolhos Bank, some cells from the northeast continental shelf and southeast margin, but gaps in occurrence were identified. High densities were estimated in the east continental margin, with the highest density in the Abrolhos Bank, in some cells of the northeast continental margin and in the southernmost area. We report that intermediate distances from the coast, and shallow waters were preferred for breeding and calving activities. We suggest that CAR models may incorporate aggregation mechanisms into habitat modeling and may provide advances in marine mammal analyses by accounting for residual autocorrelation.

Infectious Diseases in Free-Ranging Blonde Capuchins, Sapajus flavius, in Brazil - Marina Galvão Bueno; José Luiz Catão-Dias; Plautino de Oliveira Laroque; Silvio Arruda Vasconcellos; José Soares Ferreira Neto; Solange Maria Gennari; Fernando Ferreira; Marcia Dalastra Laurenti; Eufrosina Setsu Umezawa; Norival Kesper; Karin Kirchgatter; Lilian Oliveira Guimarães; et al. (International Journal of Primatology, 2017)